Hemoglobin shady grove: A novel fetal methemoglobin variant1. Issue 8 (4th March 2013) - Marks, Asher; Luo, Hong‐yuan; Chui, David H.K.; Greenberg, Jay
Abstract Recommendations by the US Department of Health and Human Services Secretary's Advisory Committee on Heritable Disorders in Newborns and Children aim to increase congenital heart disease screening by pulse oximetry in the nursery. Here, we describe a novel fetal methemoglobin variant discovered in a newborn found to have oxygen saturations significantly below normal upon pulse oximetry screening for congenital heart disease. As universal newborn screening with pulse oximetry is implemented, hereditary variant hemoglobins should be considered in the diagnostic work‐up in otherwise well newborns with low SpO2. Pediatr Blood Cancer 2013;60E55‐E56. © 2013 Wiley Periodicals, Inc.